2012
DOI: 10.1371/journal.pone.0034574
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefit of Radial Optic Neurotomy in a Rat Model of Glaucoma

Abstract: Radial optic neurotomy (RON) has been proposed as a surgical treatment to alleviate the neurovascular compression and to improve the venous outflow in patients with central retinal vein occlusion. Glaucoma is characterized by specific visual field defects due to the loss of retinal ganglion cells and damage to the optic nerve head (ONH). One of the clinical hallmarks of glaucomatous neuropathy is the excavation of the ONH. The aim of this work was to analyze the effect of RON in an experimental model of glauco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…While the nuclear staining pattern of NeuN facilitates quantification in experimental GON (Belforte et al, 2012;Buckingham et al, 2008;Diaz et al, 2005;Naka et al, 2010), its lack of RGC specificity is a limitation. While Buckingham et al (2008) proposed methods to account for amacrine cells (identified by choline acetyltransferase, ChAT, IHC) when estimating RGC loss in mice, ChAT immunoreactivity varied with age (from 3 to 16% of cells in the GCL of DBA/2J mice 3e18 months old) and strain (DBA/2 vs. C57/BL6N), hence interpretation of results from studies employing NeuN can be problematic.…”
Section: Neuronal Nuclei (Neun)mentioning
confidence: 99%
“…While the nuclear staining pattern of NeuN facilitates quantification in experimental GON (Belforte et al, 2012;Buckingham et al, 2008;Diaz et al, 2005;Naka et al, 2010), its lack of RGC specificity is a limitation. While Buckingham et al (2008) proposed methods to account for amacrine cells (identified by choline acetyltransferase, ChAT, IHC) when estimating RGC loss in mice, ChAT immunoreactivity varied with age (from 3 to 16% of cells in the GCL of DBA/2J mice 3e18 months old) and strain (DBA/2 vs. C57/BL6N), hence interpretation of results from studies employing NeuN can be problematic.…”
Section: Neuronal Nuclei (Neun)mentioning
confidence: 99%
“…1). Details about the statistics with the appropriate P values for each time point have already been given in another report 33 .
Figure 1Blood glucose levels in diabetic and lean ZDF rats. Blood glucose levels were significantly higher from postnatal week 7 till the end of the observation period.
…”
Section: Resultsmentioning
confidence: 99%
“…After fixation, the eyecups were rinsed several times with 0.1 M PB, the retinas were carefully detached with preserved orientation and threated further as whole mounts for RGC counting. The retinas were co-labelled with three different markers:Brn-3a 32,57,86 , NeuN 33 and RBPMS 34 that are known to recognize the majority of ganglion cells. The details about the primary antibodies used is given in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the optic nerve, syntaphilin IR was not co-localized with GFAP but was co-expressed with neuronal nuclei (NeuN) antigen, which is a marker for neurons ( Fig. 3) (Coelho et al, 2005;Belforte et al, 2012). Furthermore, syntaphilin co-localized with anti-post-density protein 95 (PSD 95), which is a marker for pre-synaptic sites (Fig.…”
Section: Syntaphilin Expression In the Superior Colliculusmentioning
confidence: 99%